Parental socialization styles: systematic review - Del Castillo Bancayán, Nova Stella (2019)
The socialization of parents has been identified as one of the most influential factors in psychosocial vulnerability in adolescence. This systematic review proposes the main objective of being able to recognize the various empirical studies about parental socialization styles and their various impacts on adolescent development. Research evaluating the relationships between parental socialization and adolescent development effects traditionally uses a twodimensional model with four types of parenting styles that combine the dimensions of acceptance, participation, rigor and imposition, theoretically orthogonal, obtaining four family typologies: authorized, authoritative, lenient and negligent. The performance of a systematic review was carried out under the technique of the Prism methodology. The databases used were from the Webb of Science, Cochcrane, Scielo, Redalyc, Dialnet and Google Scholar. The findings found were the following: Socialization experiences, such as the quality of parenting behaviors, are associated with adolescent behavior.